Reimagining Governor's institution and federalism - Narayan, Jayaprakash (2017)
Our constitution-makers have consciously chosen the Westminster model of government at both the federal and provincial levels. As an inevitable consequence, we have the ornamental constitutional heads of state at both levels-with largely symbolic roles, except in certain circumstances. In the science of child birth, there is a wise dictum: 'A good obstetrician is one who observes watchful expectancy and masterly inactivity.' The president and governors too are mostly expected to play the part without intervening in real governance. On occasion, a wise head of state is expected to give sage counsel to his prime minister/chief minister, and a sensible head of government would give enormous weight to such advice. It is paradoxical that the president, who is elected by both Houses of Parliament and State Legislative Assemblies, and therefore has the widest possible mandate in our polity, is really a figurehead; the governor, who is a mere nominee of the prime minister and appointed by the president and can be dismissed at will, has far greater discretion and latitude in dealing with the elected state government! Therefore, this essay examines the role of president and governors from a reformist's perspective. In particular, this essay will critically examine the negative consequences of the nominated governor serving at the pleasure of the president, and argue for reimagining federalism and governor's institution. - Reproduced.
Keywords: Federalism - India; Discretionary power - India; Governors - India; Governors